Arabic Cultural Vocabulary in Instagram Content @senmancung: Translation Strategy into Indonesian - Ilham, Muhammad Arifin; Al Farisi, Mohamad Zaka; Supriadi, Rinaldi (Study Program of Arabic Language Teaching, 2025)
This study analyzes translation strategies for Arabic culture-specific items (CSI) in Arabic language audiovisual content on the Instagram account @senmancung. The primary data consist of 12 videos selected from a total of 439 uploads through purposive sampling, based on the presence of cultural vocabulary that was manually translated by the creator (human translation). The secondary data include journals, books, and publications related to Aixelá’s (1996) CSI theory and Molina & Albir’s (2002) translation techniques. The data were examined using a content analysis approach, which involved several steps: identifying cultural vocabulary, classifying CSI types according to Aixelá (1996), and determining translation techniques based on the framework of Molina & Albir (2002). The findings reveal five cultural translation strategies, comprising two forms of conservation (intratextual gloss and linguistic/non-cultural translation) and three forms of substitution (limited universalization, synonymy, and naturalization). The most dominant technique is substitution, particularly limited universalization, which is used to adapt Arabic cultural vocabulary so that Indonesian audiences more easily understand it. These results demonstrate that translation in digital media is not merely a linguistic activity but also a process of cultural negotiation to ensure the acceptability of messages across languages.